A case of suicide by hydrogen sulphide poisoning in the UK. Issue 1 (4th January 2016) - Willder, Jennifer M; Tullett, William; Doherty, Pamela
Summary: Hydrogen sulphide is a colourless, flammable gas with the characteristic odour of rotten eggs. Inhalation of hydrogen sulphide is toxic to humans as it inhibits aerobic metabolism resulting in cellular hypoxia and lactic acidosis. Cases of hydrogen sulphide poisoning in the United Kingdom (UK) are usually occupational in nature occurring via accidental exposure in related industries. Although national statistical data identified 14 cases of suicide by hydrogen sulphide gas in England and Wales between 2001 and 2011, none of these have been previously published. We present the first case of suicide by hydrogen sulphide poisoning in the UK reported in the medical literature.